Implementation Of The Cobit 2019 Framework To Improve Information Technology Performance In Tokopedia - Wijanarko, Rendi Panca; Audina, Imelda; Eka Saputri, Dita Ayu; Nutfa Rabbanii, Nimas Adjeng; Mardi Suryanto, Tri Lathif (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2023)
The COBIT framework has evolved into COBIT 2019 and is still the most widely used framework by IT auditors who use complete or customized model components to assess IT governance in an organization or company. COBIT has made it clear that to gain a complete insight into the governance model in an organization, IT auditors must incorporate organizational culture assessment into the audit approach. This study aims to analyze the implementation of the COBIT 2019 framework to improve information technology performance in Tokopedia. This study uses a qualitative descriptive approach where data collection is carried out using primary and secondary data from direct observations of Tokopedia's e-commerce system through tokopedia.com pages and literature reviews from several relevant journal articles. The results showed that the results of the evaluation of the performance of information technology governance in the Tokpedia e-commerce system that focuses on the DSS (Deliver, Support, and Service) domain show that some e-commerce systems still do not fully carry out good information technology delivery, support, and services.